2011
DOI: 10.1074/jbc.m111.237578
|View full text |Cite
|
Sign up to set email alerts
|

Neu1 Sialidase and Matrix Metalloproteinase-9 Cross-talk Is Essential for Toll-like Receptor Activation and Cellular Signaling

Abstract: The signaling pathways of mammalian Toll-like receptors (TLRs) are well characterized, but the precise mechanism(s) by which TLRs are activated upon ligand binding remains poorly defined. Recently, we reported a novel membrane sialidase-controlling mechanism that depends on ligand binding to its TLR to induce mammalian neuraminidase-1 (Neu1) activity, to influence receptor desialylation, and subsequently to induce TLR receptor activation and the production of nitric oxide and proinflammatory cytokines in dendr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(101 citation statements)
references
References 60 publications
4
97
0
Order By: Relevance
“…It is noteworthy that we have reported a striking similarity with this novel receptor signaling platform for nerve growth factor (NGF) TrkA receptors [35], insulin [59, 60] and cell surface TOLL-like receptor (TLR)-4, [34, 6164] and intracellular TLR7 and TLR9 receptors [65], all of which require receptor dimerization and are regulated by Neu1. Pshezhetsky and Ashmarina [66] have recently summarized the emerging data demonstrating that Neu1, well known for its lysosomal catabolic function, is also localized to the cell surface and assumes the previously unrecognized role as a structural and functional modulator of cellular receptors.…”
Section: A Novel Egfr-signaling Platform and Its Targeted Translationmentioning
confidence: 99%
See 2 more Smart Citations
“…It is noteworthy that we have reported a striking similarity with this novel receptor signaling platform for nerve growth factor (NGF) TrkA receptors [35], insulin [59, 60] and cell surface TOLL-like receptor (TLR)-4, [34, 6164] and intracellular TLR7 and TLR9 receptors [65], all of which require receptor dimerization and are regulated by Neu1. Pshezhetsky and Ashmarina [66] have recently summarized the emerging data demonstrating that Neu1, well known for its lysosomal catabolic function, is also localized to the cell surface and assumes the previously unrecognized role as a structural and functional modulator of cellular receptors.…”
Section: A Novel Egfr-signaling Platform and Its Targeted Translationmentioning
confidence: 99%
“…MMP9 and neuromedin B GPCR (NMBR) are associated with each other on the cell surface, and together form a complex with EGFR [30], TrkA receptors [35], insulin receptor IRβ subunits [59], TLR-4 [34, 61, 62, 64], and TLR7 and −9 [65]. Co-immunoprecipitation experiments using cell lysates from RAW-blue macrophage cells demonstrated that the 80 kDa NMBR isoform forms a complex with the active 88 kDa MMP9 isoform from naïve or lipopolysaccharide (LPS)-stimulated cells [62].…”
Section: Gpcr Signal Integration In Receptor Tyrosine Kinase Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, TLR dimerization and activation mediates MyD88/TLR4 complex formation and activation of the transcription factor NF-κB, as seen in macrophages treated with the endotoxin LPS. LPS binding to TLR4 apparently induces the interaction of NEU1 with metalloproteinase-9 (MMP9), which in turn stimulates downstream guanine protein-coupled receptor (GPCR) signaling [76]. This NEU1-MMP9 complex was shown to bind to TLR4 on the cell surface of naïve macrophages, but the inhibition of MMP9 and GPCR Gα i -signaling proteins blocked LPS-induced NEU1 activity and downstream NF-κB activation.…”
Section: The Lmc and Its Components In Tissue And Cell Homeostasismentioning
confidence: 99%
“…Furthermore, ADAM15 has been shown to cleave the ectodomain of MMP-10 (24). Interestingly, it has been proposed that activation of MMP-9 activity may be initiated upon TLR ligand binding (25). Furthermore, TLR3 and TLR2 engagement has been shown to enhance MMP-9 and MMP-10 expression (6,26).…”
Section: Suppression Of Adam15 Expression Enhances Proinflammatory Cymentioning
confidence: 99%